A Sick Body, a Sick Mind. The Last Taboo in Biography - Renders, Hans (Dějiny – teorie – kritika, 2025)
The relationship between the personal and the public is one of the foundations of biography. To interpret the life of a public figure, the biographer will, therefore, use the personal in any case. Strangely enough, biographers rarely do this when it comes to interpreting something as personal as illness. This is especially true for a physical illness. When the mind is sick, the biographer is usually more alert. This contribution is about the disease in the biography.